Botulinum toxin injection vs topical nitrates for chronic anal fissure: an updated systematic review and meta‐analysis of randomized controlled trials. (3rd January 2018) - Sahebally, S. M.; Meshkat, B.; Walsh, S. R.; Beddy, D.
Abstract: Aim: Chronic anal fissures (CAFs) are frequently encountered in coloproctology clinics. Chemical sphincterotomy with pharmacological agents is recommended as first‐line therapy. Topical nitrates (TN) heal CAF effectively but recurrences are common. An alternative treatment modality is injection of botulinum toxin (BT) into the anal sphincter. We aimed to perform an updated systematic review and meta‐analysis to compare the effectiveness of BT and TN in the management of CAF. Method: PubMed, EMBASE and Cochrane databases were searched for relevant articles from inception until March 2017. All randomized controlled trials (RCTs) that reported direct comparisons of BT and TN were included. Two independent reviewers performed methodological assessment and data extraction. Random effects models were used to calculate pooled effect size estimates. Results: Six RCTs describing 393 patients (194 BT, 199 TN) were included. There was significant heterogeneity among the trials. On random effects analysis there were no significant differences in incomplete fissure healing (OR = 0.47, 95% CI 0.13–1.68, P  =   0.24) or recurrence (OR = 0.70, 95% CI 0.39–1.25, P  =   0.22) between BT and TN, respectively. BT was associated with a higher rate of transient anal incontinence (OR = 2.53, 95% CI 0.98–6.57, P  =   0.06) but significantly fewer total side effects (OR = 0.12, 95% CI 0.02–0.63, P  =   0.01) and headache (OR = 0.10, 95% CI 0.02–0.60, P  =   0.01) compared with TN. Conclusion: BT is associated with fewer side effects than TN but there is no difference in fissure healing or recurrence. Patients need to be warned regarding the risk of transient anal incontinence associated with BT.